2022
DOI: 10.1007/s00167-022-06867-x
|View full text |Cite
|
Sign up to set email alerts
|

Custom TKA combined with personalised coronal alignment yield improvements that exceed KSS substantial clinical benefits

Abstract: Purpose The purpose of this study was to report Knee Society Scores (KSS) at 12-month follow-up in a series of 266 knees that received custom TKA. The hypothesis was that custom TKA combined with personalised alignment would yield improvements greater than substantial clinical beneits (SCB) of KSS Knee and Function. Methods From a consecutive series of 905 patients (918 knees) that received primary TKAs, 261 (29%) patients (266 knees) received computed tomography (CT)-based posterior-stabilised cemented custom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, there are three recent comparative studies on the products of both companies, which are mostly not included in meta-analyses. They show clear advantages of CMI compared to off-the shelf implants in terms of pain, mobility, overall outcome, and satisfaction for Conformis (iTotal ® ) [ 38 , 39 , 40 ] as well as Symbios (Origin ® ), with also very promising clinical and radiological results [ 41 , 42 , 43 ]. The latter comparative studies, however, might have conflicting bias as they are at least partly sponsored.…”
Section: Knee Arthroplastymentioning
confidence: 99%
“…Furthermore, there are three recent comparative studies on the products of both companies, which are mostly not included in meta-analyses. They show clear advantages of CMI compared to off-the shelf implants in terms of pain, mobility, overall outcome, and satisfaction for Conformis (iTotal ® ) [ 38 , 39 , 40 ] as well as Symbios (Origin ® ), with also very promising clinical and radiological results [ 41 , 42 , 43 ]. The latter comparative studies, however, might have conflicting bias as they are at least partly sponsored.…”
Section: Knee Arthroplastymentioning
confidence: 99%
“…As of 2018, another CIM TKA system is available, the Symbios Origin ® implant (Symbios, Yverdon-les-Bains, Switzerland) [ 43 ]. After promising first results [ 44 ], a large improvement in the KSS was recently shown, with a mean KSS of 94 points after 1 year [ 45 ]. Another study reported a high satisfaction rate of 94% after a mean follow-up of 2.8 years [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies were not yet included, though [ 29 , 30 , 31 ]. Recent first studies with customized TKA of a second company with also partial constitutional alignment show promising results as well [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%